Metabolites changes of a low-temperature and low-salt fermented Chinese kohlrabi during fermentation based on non-targeted metabolomic analysis - Zhao, Zhiping; Chen, Hongfan; Zhang, Yulin; Nie, Xin; Xiang, Lu; Peng, Tao; Liu, Dayu; Luo, Huailiang; Wang, Aili (Frontiers in Sustainable Food Systems, 2023)
A low-temperature and low-salt industrially fermented Chinese kohlrabi (LSCK) was developed in this study, with the salt usage decreased by approximately 70% compared to the traditional high-salt fermented Chinese kohlrabi (HSCK). The differences in physicochemical properties, metabolites and overall flavors during LSCK fermented for 0, 45 and 90 days (d) were analyzed by gas chromatography-time-of-flight mass spectrometry (GC-TOF-MS), electronic nose (E-nose) and other techniques. The results showed that the total acid content increased significantly from 3.68 to 8.59 g/kg. However, the protein content significantly decreased from 2.52/100 to 0.66 g/100 g. The number of lactic acid bacteria cells increased significantly from 3.69 to 4.46 log10CFU/g. Based on multivariate statistical analysis, 21, 14, and 15 differential metabolites were identified in the three treatment groups A1 (0 and 45 days), A2 (45 and 90 days), and A3 (0 and 90 days) respectively (VIP > 1, p < 0.05, |log2FC| ≥ 1.1). Carbohydrates, sugar alcohols, amino acids and their derivatives were the main differential metabolites in the LSCKs fermented for different periods. Aminoacyl−tRNA biosynthesis and glycine, serine and threonine metabolism pathways significantly correlated with the differential metabolites based on Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis (p < 0.05). Furthermore, the overall odors were significantly different among the LSCKs with different fermentation periods, as detected by E-nose. The present study describes the change trend of metabolites during LSCK fermentation and elucidates important metabolic pathways in LSCK, providing a theoretical basis for the target regulation of functional metabolites in kohlrabi and the optimization of LSCK processing.